Wage growth in Australia: Lessons from longitudinal microdata - Dan Andrews; Nathan Deutscher; Jonathan Hambur; David Hansell (The Australian Government, The Treasury, 2019)
This paper uses novel microdata sources spanning 2001-02 to 2015-16 to explore the structural drivers of wage growth in Australia, with a view to better understanding recent weak wage growth - a phenomenon observed across a range of advanced economies. Controlling for a range of cyclical and other factors, we show that part of firms' idiosyncratic productivity growth tends to be passed-through to workers in the form of higher wage growth, consistent with the idea that firms share rents with their workers. The size of this pass-through is around the midpoint of leading international estimates, and appears to decline modestly after 2012-13, when aggregate wage growth begins to slow. We then discuss a range of possible mechanisms for this modest decline, including the transition from the mining boom, globalisation, changing shock processes, declining labour market fluidity and uneven technology diffusion. Given that our dataset does not cover the past few years, however, it is not clear whether lower pass-through of productivity to wages has persisted. In this respect, our results represent a tentative first step in examining the microeconomic drivers of a macroeconomic phenomenon with particular reference to wages. We provide a proof-of-principle demonstration of the value of longitudinal microdata and empirical techniques to such investigations, and suggest further analysis into the factors behind declining labour market fluidity would be a fruitful exercise.
Keywords: 330